Landscape Ecological Urbanism for Restoration of Pallikaranai Marsh Land, Chennai, Tamil Nadu. (2016) - Surya, S.
Abstract: This paper outlines the process by which a proposal was made to restore the Pallikaranai marsh in Chennai, Tamil Nadu, India, incorporating the principles of Landscape Ecology, Landscape Urbanism and Ecological Urbanism, all of which work towards finding ways of integrating nature with architecture and urban design. The design proposal is based on Landscape Ecological Urbanism, an approach put forth by Frederick Steiner, for planning of regions based on a sensitive approach to ecology and nature[1], and at the same time using advanced software and imaging techniques to reach an effective planning solution